THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL SELF-EFFICACY, AND SELF-CONTROL ON RISKY CREDIT BEHAVIOR OF PAYLATER USERS (Study on State University Students in Malang City) - Yoga Pratama , Dimas; Fitriyah, Fitriyah (JURNAL EKBIS, 2024)
This study aims to find empirical evidence of the effect of financial literacy, financial self-efficacy, and self-control on risky credit behavior. Because risky credit behavior can cause serious financial difficulties if a person cannot meet their debt payment obligations which have a long-term impact on credit reputation and make it difficult to get loans in the future. The population used was public university students in Malang city. The sample was selected using purposive sampling method with a total of 250. The study used multiple linear regression testing models tested with the help of SmartPLS 4.0. The results of this study indicate that financial literacy has no effect on risky credit behavior while financial self-efficacy and self-control have a positive and significant effect on risky credit behavior.